Hidden Non-Progressiveness: US Women’s Magazine Good Housekeeping During Wartime and Emancipation of Mass Media Content - Maurizi, Ester (Status Quaestionis, 2022)
This article aims to investigate whether the US women’s magazine Good Housekeeping, a massi- vely popular publication, linguistically reflected a perceived emancipation of the WWII Ame- rican woman’s identity and role at home and in the workplace. Specifically, a corpus of articles appeared on the magazine between 1920 and 1949 will be analysed using Corpus Analysis and Critical Discourse Analysis to put to the test the theory that the 1940s texts are more emanci- pated or modern than those from the previous two decades. How do their Wartime linguistic strategies compare with those from the time of peace between the Wars? And how do they compare with the real, daily life in Wartime America, as reconstructed by historians?